Pengaruh Debt To Equity Ratio, Return On Equity, Dan Earning Per Share Terhadap Return Saham - Amalia Firdaus; Sri Zulaihati; Tri Hesti Utaminingtyas (Wawasan : Jurnal Ilmu Manajemen, Ekonomi dan Kewirausahaan, 2023)
The purpose of this study is to find out there are influence between Debt to Equity Ratio (DER), Return on Equity (ROE), and Earning Per Share (EPS) on Stock Returns. The population at this study is consumer non-cyclicals sector who listed at Indonesia Stock Exchange (IDX) in 2021 with total 98 companies, using a non-probability sampling technique in the form of purposive sampling of 69 companies, due to outlier data so the total data are 64 datas. The analysis technique used is descriptive statistical analysis, requirements analysis test (normality and linearity test), classical assumption test (multicollinearity, heteroscedasticity, and autocorrelation), multiple linear regression analysis, and hypothesis test (t test, f test, and coefficient of determination test ) using the Statistical Package for the Social Sciences (SPSS) software. The results of this study are that partially DER and EPS have no effect on stock returns, ROE has an effect on stock returns, while DER, ROE, and EPS simultaneously have an effect on stock returns.